THE CONTAINER SYSTEM OF PNEUMATIC CONVEYING PIPELINE BASED ON THE USE OF WIND ENERGY - Buriak, O. O.; Dzenzerskyi, V. O.; Zeldina, E. O.; Tarasov, S. V. (Science and Transport Progress, 2007)
Based on our research of the transformation of the kinetic energy of the wind into potential energy form, a сapsule-pipe pneumatic transportation system was developed. In this system the compressor stations were replaced with the modular air streams concentrators, which create the differential pressure inside the trunk pipe-line, necessary for transporting a payload.